Fibrolamellar Carcinoma with DNAJB1-PRKACA Fusion in a 16-Year-Old: Case Report and Review of Literature - Varsha Prakash; Neha Varshney (Journal of Renal and Hepatic Disorders, 2022)
Fibrolamellar hepatocellular carcinoma (FLC) is a unique primary liver malignancy arising in noncirrhotic livers of young adults with an incidence of 0.02 per 100,000 in the USA (1). In the 5th edition of the WHO classification of the digestive system tumors published in 2019, fibrolamellar carcinoma is categorized as a subset of hepatocellular carcinoma (HCC). In 2014, the unique DNAJB1-PRKACA chimeric fusion protein was identified. Later studies proved this chimeric fusion protein as the main pathological driver in the disease manifestation of fibrolamellar carcinoma. Despite the invention of specific molecular genetic alteration in FLC, its oncogenic role and implication in FLC treatment remain an enigma. Surgical resection remains the primary therapeutic option, and the recurrence rate is extremely high (1). We present a case of fibrolamellar carcinoma in a pediatric patient with the PRKACA rearrangement resulting in DNAJB1-PRKACA fusion.